THE EXPERIENCE OF BEING A COSPLAYER: AN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS APPROACH - Ulfa Miranti; Yohanis Franz La Kahija (Jurnal EMPATI, 2018)
Cosplay is defined as the type of performing arts of an individual wearing a costume as a fictional character, usually from graphic novels, comics, anime media, cartoons, video games, or science fiction and fantasy. The method of data analysis that is used in this study is an Interpretative Phenomenological Analysis (IPA) approach. The procedure focuses on exploring the experiences, thoughts, and unique events the subject has through interviews. Subjects were selected based on following criteria: subject is a cosplayer that has been actively cosplaying for three years and has played more than five characters. The results of this study show three focus themes of character personification, self-transformation and impression for the sake of appreciation. Researchers found that whilst being a cosplayer, subjects are required to imitate the character not only in terms of visual representation but also the nature possessed by the character. Thus, this study is expected to be useful for a description of a participatory modern subculture, such as cosplay, and an understanding of people with an interest in fictional characters.